1991
DOI: 10.1182/blood.v78.10.2542.bloodjournal78102542
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the survival of mature human eosinophils: interleukin-5 prevents apoptosis in mature human eosinophils

Abstract: We and other groups have previously shown that interleukin-5 (IL-5) maintained the viability of mature eosinophils in an in vitro liquid culture system. Mature eosinophils did not proliferate but their survival was maintained in the presence of IL-5. Using this culture system, we investigated the mechanism of IL-5-mediated survival. In the absence of human IL-5 (hIL-5) mature eosinophils succumbed after 4 days, while in the presence of hIL-5 they survived up to 10 days. When DNA extracts of cultured eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 0 publications
6
58
0
5
Order By: Relevance
“…Next, we incubated freshly isolated peripheral eosinophils with IL-5, IL-13, eotaxin-3 or recombinant periostin, either singly or in combination, and assessed cell viability via 4',6-diamidino-2-phenylindole (DAPI) exclusion after 24 h in culture. As expected, eosinophils maintained in media without supplemental cytokines displayed high rates of cell death (35.4%, range 25.2-41.4%) after 24 h. In contrast, and as previously described, 33 IL-5 enhanced eosinophil survival, with significantly less cell death (11.5%, range 8.6-15.9%) after 24 h in culture (Figure 5a, b). Neither IL-13 nor eotaxin-3 enhanced eosinophil survival compared to media alone, with generally up to 40% of cells exhibiting permeability to DAPI after 24 h (Figure 5b).…”
Section: Periostin Enhances Eosinophil Survival Through Amsupporting
confidence: 86%
“…Next, we incubated freshly isolated peripheral eosinophils with IL-5, IL-13, eotaxin-3 or recombinant periostin, either singly or in combination, and assessed cell viability via 4',6-diamidino-2-phenylindole (DAPI) exclusion after 24 h in culture. As expected, eosinophils maintained in media without supplemental cytokines displayed high rates of cell death (35.4%, range 25.2-41.4%) after 24 h. In contrast, and as previously described, 33 IL-5 enhanced eosinophil survival, with significantly less cell death (11.5%, range 8.6-15.9%) after 24 h in culture (Figure 5a, b). Neither IL-13 nor eotaxin-3 enhanced eosinophil survival compared to media alone, with generally up to 40% of cells exhibiting permeability to DAPI after 24 h (Figure 5b).…”
Section: Periostin Enhances Eosinophil Survival Through Amsupporting
confidence: 86%
“…We next looked for AT-specific mechanisms to explain the local increase in eosinophil number, namely, the expression of the eosinophil growth factor, IL-5, as well as eosinophil chemokines CCL11, CCL24, CCL3, and CCL5. IL-5 is strongly linked with eosinophil function, as it regulates cellular differentiation, proliferation/apoptosis, activation, and accumulation [22,23] and was recently shown to contribute to eosinophil accumulation in AT [15]. We found that eAT of obese CCR2 2/2 mice had significantly higher Il5 expression than that of WT counterparts (Fig.…”
Section: Increased Eosinophils In At Correlate With Increased Expressmentioning
confidence: 52%
“…Unlike GM-CSF and IL-3, IL-5 is a cytokine that exhibits lineage restriction. It stimulates the proliferation, maturation, and functional activation of eosinophils (151)(152)(153)(154)(155)(156) and basophils (157)(158)(159). The major cellular source of IL-5 is T cells (160), although mast cells and to some extent eosinophils (160, 161) also produce IL-5.…”
Section: Il-5 and Its Receptormentioning
confidence: 99%